Comparison of PCRbased molecular marker analyses of Musa breeding populations - Crouch, J.H.; Crouch, H.K.; Constandt, H.; Gysel, A. van; Breyne, P.; Montagu, M. van; Jarret, Robert L.; Ortíz, R. (1999)
Progress in the breeding of plantain and banana has been restricted by the complex genetic structure and behaviour of cultivated polyploid Musa. Genetic improvement has been hindered due to the large amount of space required for growth and maintenance of plant populations, in addition to the long growth cycle and the low levels of fertility and seed viability characteristic of cultivated genotypes. Molecular marker assisted breeding has the potential to dramatically enhance the pace and efficiency of genetic improvement in Musa. This study was conducted to compare different PCR-based marker systems (RAPD, VNTR and AFLP) for the analysis of breeding populations generated from two diverse Musa breeding schemes. All three assays detected a high level of polymorphism between parental genotypes and within progeny populations. As expected, AFLP assays had by far the highest multiplex ratio while VNTR analysis detected the highest levels of polymorphism. AFLP analysis of a full-sib tetraploid hybrid population confirmed previous reports based on VNTR analysis, of a high frequency of recombination during 2n (3x) gamete formation by a triploid plantain landrace. In addition, both VNTR and RAPD analyses of a full-sib triploid hybrid population suggested a high frequency of homoeologous recombination during n (2x) gamete formation by tetraploid hybrids. In general, there was a poor correlation between estimates of genetic similarity based on different types of marker. The implications of these findings for the molecular breeding of Musa crops are discussed.